SETTLEMENT REDUCTION UNDERNEATH SURFACECIRCULAR FOOTING RESTING ON REINFORCEDSOILS. (Journal of Engineering, 2007)
An analytical approach, adopted to find the settlement of foundations resting on reinforced soil based on the test results on a model surface circular footing resting on reinforced soil, is summarized. The soil was reinforced using biaxial geomesh. The settlement was determined by considering the compatibility of strain (settlement) between soil and reinforcement element underneath the foundation. Theoreticalequations were used to estimate the settlement either from the superstructure loads or from in-situ plate load tests on the reinforced soil system. The type of geomesh used in this study has been determined based on the grain size distribution of the soil. Theinvestigation in this study used two different types of geomesh. Uniformly graded sand was used to make it easier to control the density and fabric in different tests. It was found that initial horizontal and vertical movement of the reinforcement is needed to mobilize the reinforcing strength. Further, the initial settlement at small loads couldbe avoided when the reinforcement was placed closer to the base of the footing and there was an improvement in the bearing capacity value of the footing. When the reinforcement is placed away from the base of the footing(greater than B), the initial settlement decreased with a slight improvement in the bearing capacity compared with that of unreinforced soil. Non-dimensional factors were developed for settlement calculations based on the experimental test results from a series of laboratory tests on the model footing. Additional tests were performed on the model footing to evaluate the effect of the number of reinforcement layers and the depth of the top most reinforcement layer on the settlement and the improvement in the bearing capacity ofthe footing-reinforced soil system.